2010
DOI: 10.1111/j.1365-3164.2009.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Group 1 and 2Dermatophagoideshouse dust mite allergens in the microenvironment of cats

Abstract: House dust mite allergens (HDMAs) are some of the most common allergens associated with allergic diseases in humans and dogs. The purpose of this study was to determine whether HDMAs could be detected in cat-associated household microenvironments. From 50 cat-only households with 95 cats, dust samples were collected by vacuuming for 2 min m(-2) from three areas where cats slept or rested regularly from September to October 2006. Relative humidity and temperature were measured in each household using a data log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
(148 reference statements)
0
12
1
Order By: Relevance
“…From 50 cat-only households with 95 cats, dust samples, by use of by vacuuming from areas where cats slept/rested, were analyzed via ELISA for Der p 1, Der f 1 and HDM group 2 allergens. Out of 50 households 38 were greater than 2 micro gr (-1) of dust for at least one HDMA (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 50 cat-only households with 95 cats, dust samples, by use of by vacuuming from areas where cats slept/rested, were analyzed via ELISA for Der p 1, Der f 1 and HDM group 2 allergens. Out of 50 households 38 were greater than 2 micro gr (-1) of dust for at least one HDMA (19).…”
Section: Discussionmentioning
confidence: 99%
“…Latter data should lead to further determination of the role of HDMs in cats suffering from putative allergic conditions such as atopic dermatitis or asthma (19). In the present study a statistical significance for specific IgE levels between healthy controls and allergic cats against house dust mites 0.21±0.018 vs 4.69±1.49 (kU/l) for D. farinae (p=0.0001) and significant alterations between healthy controls and allergic cats 0.21±0.023 vs 3.11±1.21 (kU/l) (p=0.003) for DP.…”
Section: Discussionmentioning
confidence: 99%
“…). Treatment of pets with insecticides such as Fipronil is known to be an effective acaricide (Coleman & Atwell, ), while flea control agents have been associated with lower levels of Der p 1 in the microenvironments of dogs (Raffan et al , ) and cats (Loft & Rosser, ). However, questionnaire respondents indicated that none of the pets examined in this study had been treated with any kind of insecticide or acaricide, thus ruling out any acaricidal effect on mite densities and allergen levels in samples from HP.…”
Section: Discussionmentioning
confidence: 99%
“…The AD in cats is not necessarily connected with the levels of IgE or the diagnosis of specific IgE antibodies in serum [ 49 ]. IgE to environmental allergens including pollen can be even found in pathogen-free housed cats [ 50 , 51 ]. When two groups of 10 cats each were intradermally tested, immediate reactivity was reported as IgE- as well as IgG-mediated reaction, but also explained by nonspecific mast cell degranulation [ 52 ].…”
Section: Reviewmentioning
confidence: 99%
“…Even in early studies specific IgG directed against ryegrass pollen, in addition to flea and house dust mite allergens, was reported and proposed as the second Th2 antibody class of relevance in feline allergy [ 53 ]. Rather than pollen, house dust mite allergens are found abundantly in the sleeping places of cats, but are not yet definitely proven to be causative allergens in feline AD or asthma [ 51 ].…”
Section: Reviewmentioning
confidence: 99%